Visions of Freedom - Gleijeses, Piero
During the final fifteen years of the Cold War, southern Africa underwent a period of upheaval with dramatic twists and turns in relations between the super powers. Americans, Cubans, Soviets, and Africans fought over the future of Angola, where tens of thousands of Cuban soldiers were stationed and over the decolonization of Namibia. Beyond lay the great prize: South Africa. This book provides an international history of this important theater of the late Cold War.